Perencanaan dan Pembuatan Sistem Deteksi Tingkat Kelelahan Pada Pengemudi Kendaraan Bermotor - Muhammad Taufiq Tamam; Itmi Hidayat Kurniawan; Anis Kusumawa (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2022)
Traffic accidents on the highway are common. One of the causes is the fatigue factor of the driver so that his driving concentration will decrease. The condition of fatigue in the driver occurs due to decreased levels of oxygen in the blood (SpO2). This application to monitor the driver's fatigue level is done by installing a heart rate sensor and blood oxygen saturation (SpO2) on the driver's wrist. The measurement results are displayed on an OLED screen that contains the condition of the heart rate, oxygen saturation (SpO2) and the level of fatigue. If the fatigue level is at a high level then there will be a warning. Based on the results of trials that have been carried out, the average heart rate measurement error is 1.08% and the oxygen saturation in the blood (SpO2) is 0.81%.